E-platform for easy learning anywhere and anytime : Andriod application - Sun, Shuai (Nanyang Technological University, 2021)
As the COVID-19 rages around the world, a large number of schools, universities, and training centers are closed, which adversely affects a large number of young people who are going to school or combining industry and education. Easy Learning is an Android application platform designed to help people who stay at home can use their smartphones to study anytime, anywhere, and course providers can also use their smartphones to upload courses anytime, anywhere. Skill seekers can search for courses that match their interests, as well as keywords directly. Course providers can be mature companies and government agencies or experienced individuals, bridging the information gap between everyday individuals seeking to learn new skills or hobbies and course providers. In addition to providing online courses for our skill seekers, this Android application platform also provides onsite courses release channels. The nearest onsite course provider can be found through the determined MRT station. For course providers, this Android mobile application will become a cost-effective course publishing platform for small businesses and individual. It takes very little effort to develop and take the lead in implementing their marketing strategies to attract the attention and interest of the target audience.